2022
DOI: 10.1111/aphw.12384
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' physical activity after lockdown: Testing the health action process approach and the moderating role of fear of Covid‐19

Abstract: The coronavirus pandemic has influenced many lives, particularly older adults'. Although isolation protects from infection, health behaviors like physical activity (PA) are important to reinstate after lockdown. However, fear of Covid‐19 may act as a barrier, for example, by preventing people from going outside. Based on the health action process approach (HAPA), we investigated whether and why older adults' PA changed after lockdown, and whether fear of Covid‐19 moderates the intention–behavior relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Post COVID-19 research suggests that these behaviors during confinement are critical in remaining consistent with healthy behaviors after lockdown. For example, in one study older adults who were physically active during lockdown are more likely to facilitate exercise post lockdown ( 45 ). In another, the learning of new technologies during the stay at home period increased intention to use social networking sites, with a jump from 27% pre-restrictions to 50% after restrictions eased ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post COVID-19 research suggests that these behaviors during confinement are critical in remaining consistent with healthy behaviors after lockdown. For example, in one study older adults who were physically active during lockdown are more likely to facilitate exercise post lockdown ( 45 ). In another, the learning of new technologies during the stay at home period increased intention to use social networking sites, with a jump from 27% pre-restrictions to 50% after restrictions eased ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, however, in contrast to young people, PA levels in older adults are increasing and have reached levels higher than before the pandemic (Sport England, 2023a). It is noteworthy that a study of older adults in German‐speaking parts of Europe found that increased feelings of self‐efficacy and positive outcome expectancies regarding the health benefits of PA significantly predicted participants' intention to remain active postlockdown (Bösch & Inauen, 2023). Another potential reason for the increase in PA in older adults could be due to public health messaging campaigns around the importance of keeping active for those at increased risk of cognitive decline and physical health issues.…”
Section: The Impact Of the Pandemic On Global Exercise Patternsmentioning
confidence: 99%
“…Subsequently, people prepare themselves to adopt a certain behavior and make decisions related to it. After the formation of behavioral intention, people enter the volitional stage, which consists of the constructs of action and coping plan, and maintenance and recovery self-efficacy [12,13]. The HAPA model has been used many times to describe variables affecting physical activity in different groups such as patients with diabetes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%